The preparation and characterization of electrospun chitosan-gelatin nanofibers containing copper-metal-organic frameworks loaded with curcumin and chrysin as antibacterial wound dressings - Soo, Ghee Yeoh; Yun, Khoon Liew; Wei, Meng Lim; Abdul Rahman, Norizah; Yoon, Yee Then (American Chemical Society, 2025)
An electrospun chitosan-gelatin (CS-GL) nanofiber encapsulated with the curcumin (CUR)-chrysin (CHR)-loaded copper (Cu) metal-organic framework (MOF) was successfully synthesized in this study. A high percentage of encapsulation efficiency (99.2%) of CUR and CHR in Cu-MOF-CUR-CHR was yielded. Other than the confirmation of the successful fusion of MOFs with CUR-CHR in CS-GL/Cu-MOF-CUR-CHR nanofibers using Fourier-transform infrared (FTIR) spectroscopy, the scanning electron microscopy (SEM) images depicted an average diameter in the range of 302-380 nm. The percentage of cumulative drug release of CS-GL/20% Cu-MOF-CUR-CHR nanofibers in phosphate-buffered solution at pH 7.4 after 48 h was 98.9%, which was higher than CS-GL/CUR-CHR nanofibers without Cu-MOFs. In the cytotoxicity test on Human epidermal keratinocytes cell line cells, it was noticed that 1% and 5% CS-GL/Cu-MOF-CUR-CHR nanofibers exhibited high cell survival (>90%). Through the colony counting method, the logarithm reduction values (LRVs) of CS-GL/5% Cu-MOF-CUR-CHR nanofibers were 2.69 against Staphylococcus aureus and 1.87 against Pseudomonas aeruginosa. It was noteworthy that the CS-GL/Cu-MOF-CUR-CHR nanofiber exhibited a higher antibacterial activity against Gram-positive than Gram-negative bacteria. Overall, the biocompatible CS-GL/Cu-MOF-CUR-CHR nanofibers with an effective antibacterial effect have the potential to be used as an alternative to antibiotics in antibacterial wound dressing applications.